EXAMINING OPERATING PERFORMANCE IN AN INSULAR BANK OLIGOPOLY THE CASE OF PUERTO RICO - Herrera, Jorge C. (Digital Repository of Theses, 2022)
This study examines the operating efficiency of the Puerto Rican banking sector as it coalesced into an oligopoly. Notably, contravening institutional precepts, consolidation activity was sanctioned by a regulator overtly concerned with stemming rapidly deteriorating macroeconomic conditions. No other research is known to have investigated the locality’s unique circumstances nor a dramatically contracting marketplace in the United States. Statutory guidelines designed to preclude excessive market concentration ensure the sui generis nature of the setting. The main research questions considered are whether the emergence of an oligopoly affected the system’s operating performance, were institutions impacted in a similar manner, and was the regulatory objective of concocting a more resilient banking sector achieved. To address these inquiries, the dissertation is guided by the conceptual framework advanced by real resource theory, as manifested by both the intermediation and production approaches. Performance of the banking system is measured by applying quantitative methods designed to gauge the individual participants’ ability to convert or transform inputs into outputs. The non-parametric approach advanced by Data Envelopment Analysis estimates the operating efficiencies for each commercial bank. The Malmquist Total Factor Productivity Index then segregates the contributors to performance between technological innovation and managerial effectiveness. Finally, the parametric method associated with the Tobit model assesses the relative contribution to productivity of specific endogenous and exogenous parameters. Congruous with recent research devoted to oligopolistic market structures, the results reveal an improvement in systemic performance although with asymmetric reverberations. Consequently, for policymakers, the study concludes that under certain conditions fomenting a highly concentrated marketplace is advisable. However, heightened monitoring would be warranted to prevent abusive anti-competitive practices. For practitioners, the findings highlight the importance of technology implementation in driving performance and advocate particular close scrutiny of expenses pertaining to interest cost and premises on account of their assessed statistically significant contribution to profitability.